Factors affecting customers' online purchasing behaviour: the mediating role of purchase intention / Abdul Kadir Othman... [et al.] - Othman, Abdul Kadir; Wan Taha, Nur Ain; Omar, Nur Asmahani; Radzuan, Nur Fadhilah; Che Mat, Siti Noor Afiqah; Mohd Hanipiah, Siti Nur Fatanah (UiTM Cawangan Johor, 2019)
Online purchasing is a global phenomenon that is growing rapidly. The purpose of this study is to investigate how internet is used as a strategic tool that affects customer online purchasing behaviour among online purchasers in Malaysia. This study used correlational designas it describes the significant variables that relate to customer online purchasing behavior. The method used in this study is a quantitative approach using a questionnaire as a data collection tool. The data were collected using online means and analysed using correlation and regression analyses. The findings of the data revealed that all the independent variables are significant to influence the dependent variable (customer online purchasing behaviour). Purchase intention mediates the relationship between website quality and online purchase behaviour and the relationship between security and online purchase behaviour. This study provides implications to sellers to improvise their methods when selling their products online.